(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines theoretical approaches to defining historical and cultural heritage, analyzes its structure and social value, and identifies its place within the system of tourism resources. Particular attention is paid to the relationship between tangible and intangible heritage, the legal interpretation of the category of a «cultural heritage object», and the role of heritage as a mechanism for preserving historical memory, cultural identity, and sustainable territorial development. Using the example of Uzbekistan, the study demonstrates that historical and cultural heritage is not only an object of protection, but also a significant intellectual, educational, and economic resource shaping the prospects for the development of cultural tourism.